PANDANGAN HUKUM INTERNATIONAL ATAS REKLAMASI PANTAI TERHADAP RENEGOSIASI BATAS WILAYAH INDONESIA (STUDI KASUS INDONESIA DAN NEGARA TETANGGA) - Azmi, M. Rizqi (Lembaga Marwah Rakyat, 2023)
Coastal reclamation will have an impact on social, environmental, legal and economic activities, and will even spur the development of other supporting infrastructure. With reclamation, it is hoped that the need for land will be met, but on the other hand it can have a big impact. One of them is territorial boundary conflicts due to reclamation activities. The form of territorial boundaries between countries is determined by international law, such as the 1982 United Nations Convention on the Law of the Sea, based on principles of justice accepted by all countries. Many border disputes between countries are brought to international arbitration bodies or tribunals. This judicial decision gave rise to the principle of impartiality in border decisions. This is often reaffirmed by multilateral agreements Negotiation. National territorial boundaries are important for the implementation of their rights and obligations under national and international law. The boundaries of national territorial waters are determined by the United Nations Convention on the Law of the Sea of ​​1982, the Geneva Convention on the Law of the Sea of ​​1958 and other areas. However, the Geneva Conventions do not have a legal document defining the territorial restrictions of island states.